Contemporary Management - Jones,Gareth R. (McGraw-Hill Education, 2018)
Provide students with an account of the changes taking place in the world of business management. It shows the changes taking place in management practices by incorporating recent developments in management theory, research, and by providing vivid, current examples of how managers of companies large and more.